2021
DOI: 10.1155/2021/5298890
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Evolutionary Game and Simulation Analysis of Coal Mining Safe Production Supervision under the Chinese Central Government’s Reward and Punishment Mechanism

Abstract: In recent years, although coal mine accidents in China have decreased, they still occur frequently. Most previous studies on the evolutionary game of safety mining are limited to a focus on system dynamics and two-party game problems and lack a spatial graphic analysis of strategy evolution. The parameters adopted are too few, and the influencing factors considered are too simple. The purpose of the paper is to introduce more parameters to study which will have an important impact on the strategy choices of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Hypothesis 4. There is a cost to the government when it adopts regulation, C g (Zhu et al, 2021). Under government regulation, polluting enterprises will be fined F e if they are not insured, and insurance companies will likewise be fined F i if they choose not to underwrite.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…Hypothesis 4. There is a cost to the government when it adopts regulation, C g (Zhu et al, 2021). Under government regulation, polluting enterprises will be fined F e if they are not insured, and insurance companies will likewise be fined F i if they choose not to underwrite.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…According to Lyapunov's frst method [37], if all eigenvalues of the Jacobian matrix in Table 3 have negative real parts, the equilibrium point is asymptotically stable, and if there are one or more eigenvalues with positive real parts at the equilibrium point, then the equilibrium point is unstable. Terefore, we can obtain the stability analysis of the equilibrium points, which are listed in Table 4.…”
Section: Stability Analysismentioning
confidence: 99%
“…Egilman et al (2007) argued that the vulnerability of drug safety regulation to capture is due to the lack of involvement of other interested parties. Zhu and Rong (2021) found that rent-seeking exists in drug testing and constructed a three-way evolutionary game model among drug manufacturers, third-party drug testing organizations and government regulators. Limited studies have focused on drug safety regulatory capture.…”
Section: Drug Safety Regulationsmentioning
confidence: 99%
“…The key factors affecting the behavioral strategy characteristics of drug regulatory authorities and drug companies throughout the drug regulatory authorities and drug companies in drug safety regulation. A certain intensity needs to be satisfied, and after repeated games, the prevention of regulatory capture strategy will gradually stabilize, as the dynamic stability strategy proposed by Zhu and Guo (2017). Only when drug companies regulate production and are concerned about the risk of loss, the Drug Enforcement Administration severely punishes and implements an aggressive regulatory strategy.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation